A light‐activated amnion wrap strengthens colonic anastomosis and reduces peri‐anastomotic adhesions. Issue 5 (21st March 2016) - Senthil‐Kumar, Prabhu; Ni, Tao; Randolph, Mark A.; Velmahos, George C.; Kochevar, Irene E.; Redmond, Robert W.
Abstract : Background and Objective: Colonic anastomotic failure is a dreaded complication, and multiple surgical techniques have failed to eliminate it. Photochemical tissue bonding (PTB) is a method of sealing tissue surfaces by light‐activated crosslinking. We evaluated if a human amniotic membrane (HAM), sealed over the anastomotic line by PTB, increases the anastomotic strength. Study Design: Sprague–Dawley rats underwent midline laparotomy followed by surgical transection of the left colon. Animals were randomized to colonic anastomosis by one of the following methods (20 per group): single‐layer continuous circumferential suture repair (SR); SR with a HAM wrap attached by suture (SR+ HAM‐S); SR with HAM bonded photochemically over the anastomotic site using 532 nm light (SR+ HAM‐PTB); approximation of the bowel ends with only three sutures and sealing with HAM‐PTB (3+ HAM‐PTB). A control group underwent laparotomy alone with no colon resection (NR). Sub‐groups ( n  = 10) were sacrificed at days 3 and 7 post‐operatively and adhesions were evaluated. A 6 cm section of colon was then removed and strength of anastomosis evaluated by burst pressure (BP) measurement. Results: A fourfold increase in BP was observed in the SR+ HAM‐PTB group compared to suture repair alone (94 ± 3 vs. 25 ± 8 mm Hg, P  < 0.0001) at day 3. At day 7 the burst pressures were 165 ± 40 and 145 ± 31 mm Hg ( P  = 1), respectively. A significant decrease in peri‐anastomotic adhesions was observed in the SR+ HAM‐PTB group compared to the SR group at both time points ( P  < 0.001). Conclusion: Sealing sutured colonic anastomotic lines with HAM‐PTB increases the early strength of the repair and reduces peri‐anastomotic adhesions. Lasers Surg. Med. 48:530–537, 2016. © 2016 Wiley Periodicals, Inc.